2020
DOI: 10.1111/jace.16988
|View full text |Cite
|
Sign up to set email alerts
|

Porous SiOC monoliths with catalytic activity by in situ formation of Ni nanoparticles in solution‐based freeze casting

Abstract: Micro‐ and macroporous monoliths with in situ formed nickel nanoparticles were prepared for the first time by the combination of solution‐based freeze casting and preceramic polymers (methyl polysiloxane). This one‐step process results in macroporous monoliths composed of microporous and catalytic active nickel‐containing polymer‐derived ceramic. Four different complexing and cross‐linking siloxanes with amino functionality were screened for their ability to create small nickel particles. TEM analysis confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Micro-mesoporous PDCs with high surface areas have been reported as promising catalytic supports. [18][19][20] For instance, metal-containing (e.g. Co and Ni) SiOC nanocomposites with hierarchical porosity, derived from polysiloxanes polymers, show high catalytic activity for CO2 methanation and Fischer-Tropsch Synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro-mesoporous PDCs with high surface areas have been reported as promising catalytic supports. [18][19][20] For instance, metal-containing (e.g. Co and Ni) SiOC nanocomposites with hierarchical porosity, derived from polysiloxanes polymers, show high catalytic activity for CO2 methanation and Fischer-Tropsch Synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Co and Ni) SiOC nanocomposites with hierarchical porosity, derived from polysiloxanes polymers, show high catalytic activity for CO2 methanation and Fischer-Tropsch Synthesis. 18,[20][21][22][23][24] Similarly, some transition metalscontaining (e.g. Cu, Ru, Pd, and Ir) SiCN nanocomposites have been reported as heterogeneous catalysts for liquid-phase oxidation, 25 hydrogeneration, 26,27 and sustainable synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…There is still room for further study on optimizing hydrogen adsorption-desorption properties by controlling several material parameters such as the chemical composition and micro/ mesoporosity. Moreover, the unique H2-affinity of present SiAlN suggests other applications such as a novel non-oxide catalysis support which is recently highlighted for the impressive catalytic activities in hydrogenation of polymer derived transition metal/Si-based non-oxide ceramic nanocomposites of palladium silicide containing SiCN by Motz and Kempe et al, 20 and Ni-SiOC by Wilhelm and Rezwana et al, 21 or Pt-TiN/Si3N4 nanocomposites which in our very recent study 22 showed enhanced catalytic performance for dehydrogenation of sodium borohydride in water. Therefore, polymer-derived amorphous SiAlN ceramics are expected to have an impact on catalytic processes as a transition or noble metal-free advanced material and be of significant interest for clean energy applications such as advanced hydrogen production, storage and transportation systems.…”
Section: Discussionmentioning
confidence: 99%
“…Through a precursor route called polymer-derived ceramics (PDCs), [13][14][15][16][17][18][19][20][21][22] we recently demonstrated 19 the in situ growth of nanostructured AlN into a robust, protecting silicon carbide (SiC) matrix to form amorphous single-phase Si-Al-C-N ceramics at low temperatures and an AlN/SiC solid solution at high temperatures. By changing the nature of the atmosphere (ammonia instead of nitrogen) and considering the same commercially available poly(vinylmethyl-co-methyl)silazane (Durazane® 1800, silicon nitride precursor) chemically cross-linked with N,Ndimethylethylaminealane (EtNMe2$AlH3), we have designed a novel amorphous single-phase ceramic based on the Si-Al-N system at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the shapes of polymers could be tailored according to specific requirements after pyrolysis. At present, the most widely studied PDCs systems are mainly PDCs-SiC [5][6][7][8][9][10][11][12], PDCs-SiOC [13][14][15][16][17][18][19][20][21][22], and PDCs-SiCN [23][24][25][26][27][28][29][30][31][32] systems.…”
Section: Introductionmentioning
confidence: 99%